(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the issues of Uzbekistan’s close neighborhood and cooperation based on mutual trust in the system of modern international relations. Issues of development, strengthening and improvement of Uzbekistan’s cooperation with the countries of Central Asia in a new spirit according to the system of modern international relations are analyzed from a comparative and historical point of view. A historical and comparative analysis of the fact that Uzbekistan began to pay special attention to the issues of cooperation with the countries of Central Asia was reflected in a number of initiatives put forward by Uzbekistan. In particular, the proposal of the head of Uzbekistan to regularly organize meetings on mutual consultations of the heads of Central Asian countries was put forward. As a result of this initiative being supported by all countries and international organizations, it was explained that a new era has begun in the cooperation of Uzbekistan with the countries of Central Asia. In particular, by effectively using the transport and transit potential of Central Asia in the system of modern international relations, turning the widely developed and integrated transport system into an important transit "hub" of the Eurasian continent; It is justified that proposals such as ensuring the operation of existing transport corridors and infrastructure, including the ports of the Caspian Sea, large cross-border logistics centers at full capacity, finding a joint solution to environmental issues, will serve to ensure and strengthen the economic stability of the region. . Conclusions on the development of cooperation based on close neighborliness and mutual trust were given and suggestions were put forward.